TA`BÃR SHAFAWÃ: METODE DAN TEKNIK PENGAJARANNYA - Asmawi, Muhammad Nur (Hunafa: Jurnal Studia Islamika, 2009)
This paper deals with the method and technique of teaching taâbÃ®r shafawÃ® (oral expression). The instruction of speaking skill is one of the essential parts of in the teaching of foreign language. In many educational institutions, the teaching of speaking skill seems to be more dominant than other skills. The objective of teaching taâbÃ®r shafawÃ® is to develop studentsâ competence to communicate using target language in real-life situation. A mastery of grammar in teaching taâbÃ®r shafawÃ® is not emphasized, but it focuses more on reproducing expressions in accordance with the context. The main objective of teaching taâbÃ®r shafawÃ® is to be proficient in communicating ideas and messages to other people.Kata Kunci: Â Â  ta`bÃ®r Â shafawÃ®, metode, teknik, pengajaran bahasa Arab